IMPLICIT LEADERSHIP THEORIES, CONTEXT AND LEADERSHIP POSITION - Castro Solano, Alejandro (Anales de Psicología / Annals of Psychology, 2006)
Different prototypes of leaders exist in the organizations. These leadership prototypes are linked to organizational culture and accepted cultural norms. Persons are categorized as leaders on the basis of the perceived match between their behavior and the prototypic attributes of a preexisting leader category in the mind of the followers. These categories are modeled by the organizational culture and societal practices. The main goal of this study consists on finding individual differences between military and civilian environments on implicit leadership theories. It was also analyzed individual differences between people placed in leadership positions (leaders) and subordinates (followers). The last goal was to verify whether implicit leadership theories are influenced by organizational culture perception. Participants in the study were: a) Civilians: 1003 male adults and women (31%, leaders and 69%, followers). B) Military cadets: 488, mostly males (37%, leaders and 63%, followers). Instruments used were a list of adjectives internationally used to assess implicit leadership theories, a questionnaire to describe organizational culture (Bass & Avolio, 1992). Results confirmed individual differences between military and civil contexts, for leaders and followers. Military cadets perceived the ideal military leader as a more self oriented person, making decisions without taking consideration of followers´ opinions. Civilian followers considered that an effective leader had to be participative, democratic, with high consideration of the follower. These characteristics resulted much less important for military than for civilian population.